2019
DOI: 10.3389/fnins.2019.00629
|View full text |Cite
|
Sign up to set email alerts
|

Altered Insulin Signaling in Alzheimer’s Disease Brain – Special Emphasis on PI3K-Akt Pathway

Abstract: Alzheimer’s disease (AD) and type 2 diabetes (T2D) are both diseases with increasing prevalence in aging populations. T2D, characterized by insulin resistance and defective insulin signaling, is a common co-morbidity and a risk factor for AD, increasing the risk approximately two to fourfold. Insulin exerts a wide variety of effects as a growth factor as well as by regulating glucose, fatty acid, and protein metabolism. Certain lifestyle factors, physical inactivity and typical Western diet (TWD) containing hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
220
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(227 citation statements)
references
References 81 publications
4
220
1
2
Order By: Relevance
“…In the context of AD, the loss of sphingosine kinase 2 activity and SP1 production are key pathogenic drivers of Aβ-mediated neurodegeneration [36]. Another upregulated pathway of interest is PI3K-AKT signaling, which has been extensively implicated in the pathogenesis of AD given its crucial role mediating insulin effects in the brain and other functions in microglia and astrocytes [37]. Collectively, our results from the network analysis support STAT3 as an important transcriptional regulator in AD.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In the context of AD, the loss of sphingosine kinase 2 activity and SP1 production are key pathogenic drivers of Aβ-mediated neurodegeneration [36]. Another upregulated pathway of interest is PI3K-AKT signaling, which has been extensively implicated in the pathogenesis of AD given its crucial role mediating insulin effects in the brain and other functions in microglia and astrocytes [37]. Collectively, our results from the network analysis support STAT3 as an important transcriptional regulator in AD.…”
Section: Discussionmentioning
confidence: 60%
“…This is not surprising since protein kinases in this pathway regulate many cellular activities including cellular differentiation, proliferation, apoptosis, inflammation, and innate immunity [45]. In AD, the crosstalk between insulin and MAPK signaling pathways may play a role in the disease pathogenesis [37,46]. Similar pathways crosstalk may be involved in the pathogenesis of FTD.…”
Section: Discussionmentioning
confidence: 99%
“…5D). Decreased levels of PI3K subunits, as well as blunted AKT kinase phosphorylation, have been observed in the brain of AD patients [64]. Insulin-like growth factor-2 (IGF-2) was reported to attenuates memory decline and amyloid plaques plaque formation in AD mouse model by activating the PI3K/AKT/CREB signaling pathway [65]., and insulin has been observed to promote neuron growth and synapse formation through the PI3K signal pathway [64,66].…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies have found a significant 247 correlation between peripheral insulin resistance and brain Aβ levels as measured by 248 Pittsburgh compound B-positron emission tomography (PiB-PET) [42,43]. The impaired 249 insulin-PI3K-Akt signaling observed in the AD brain has led to clinical trials studying 250 whether the enhancement of this pathway using intranasal insulin (IN) treatment is 251 beneficial [44]. Other enriched pathways that are previously reported with a key role in 252 AD include Focal adhesion [45], Ras signaling pathway [46], ECM-receptor interaction [47], 253 MAPK signaling pathway [48], Rap1 signaling pathway [49], etc.…”
Section: Pathway Enrichment Analysis 240mentioning
confidence: 99%
“…Compared to individual mutations, genes or proteins identified using 42 traditional methods, such connected pattern can help improve not only the reliability of 43 identified biomarkers, but also their replicability and interpretability. 44…”
mentioning
confidence: 99%